RO Water Poisoning By Salmonella Typhi among Children under Twelve Years in Fatima AL- Zahraa Hospital at Baghdad: An In Vitro Study - Kadhim Hindi, N ada Khazal; K. Hindi, Shatha Khazal; Khazaalwaad, Ammar; Radhi, Mohammed Malih; AL-Jubori, Rusull Hamza Kh; Ghasan, Hind; Hamza, Nawfel Fadhil (International Journal of Psychosocial Rehabilitation, 2020)
In this paper we evaluated the of RO Water Poisoning by Salmonella Typhi among Children under 12 Years, Antimicroborial Activity of plant extracts and antibiotics against S. typhi in Fatima AL- Zahraa Hospital Analytical study has been conducted during January to July 2019. The study was carried out in Fatima AL-Zahraa Hospital in Baghdad province. A total of 966 of blood samples from children under 12 years (they were drank RO water) were collected from them who were attending to the Hospital with signs and symptoms of poisoning. The samples were cultured (3 times) on different media. Antimicrobial activity of extracts and antibiotics carried out by well diffusion method, The results depicts that (12%) were positive culture for microbes bacteria, among those positive culture, the Salmonella typhi were the most common bacteria transmit after RO water filtering. The maximum effects of garlic and lemon extracts rather than antibiotics were observed in S. typhi. It is conclude that children who attending the hospital and suffers from signs and symptoms of poisoning and who drinking RO water were have been risks for contaminated mostly with Salmonella Typhi bacteria. Based on our findings and their support, it is need to be replace water filters frequently or boil water to prevent those risks. Garlic and lemon extracts exhibit obvious antibacterial properties against bacteria. The effect of extract has ability to subside the growth of infectious pathogens which have antibiotics resistance.